Pharmaceuticals in farms and surrounding surface water bodies: hazard and ecotoxicity in a swine production area in Costa Rica - Ramírez Morales, Didier Daniel (2021)
The presence of pharmaceuticals in the environment is known to have multiple origins; livestock activities comprise one scarcely studied source, both globally and specially in Latin-America. This work aims to study the occurrence of pharmaceuticals in wastewater from swine farms and their surrounding surface waters, in a highland livestock production area of Costa Rica. The monitoring of 70 pharmaceutical active compounds resulted in the detection of 10 molecules in farm wastewater (influents and effluents of the on-farm treatment system), including compounds of animal and human use. A 57% of effluents showed high hazard (ΣHQ > 1), mainly due to the compounds risperidone, ketoprofen, ibuprofen and naproxen. Additionally, ecotoxicological tests with Daphnia magna and Microtox classified at least 21% of the effluents as very toxic (10 < TU ≤ 100); likewise, 86% of effluents exhibited germination index (GI) inhibition values over 90% for Lactuca sativa. Seven molecules were detected in surface water, six of them of human use (1,7-dimethylxanthine, caffeine, cephalexin, carbamazepine, gemfibrozil, ibuprofen) and one (acetaminophen) of dual (human and veterinary) use; nonetheless, most of the detections were found in sampling points closer to human settlements than animal farms. Considering the set of molecules and their distribution, the livestock influence on surface water seems minimal in comparison with the urban influence. Only 16% of surface water samples showed high risk, mainly due to ibuprofen, gemfibrozil and caffeine; similarly, 45% samples presented GI inhibition >20% (no toxicity was determined towards Daphnia magna or Microtox). These findings in surface water suggest an incipient environmental risk in the area.